Supplementation with dehydrated coffee pulp in dairy cows and its effect on productive performance - Fernández-Navarro, Ana Laura (2024)
The effect of including dehydrated coffee pulp in the diets of dairy cows in a grazing system, in Copey of Dota area of San Jose, Costa Rica, was evaluated. The experiment was conducted with 30 cows grouped according to similar characteristics in terms of birth number, milk production, days in milk, and body condition score. Three treatments with 10 repetitions each were used: Non-supplemented control, Treatment 1 (1 kg as fed of coffee pulp/animal/day replacing 1 kg of ripe banana peel), and Treatment 2 (2 kg as fed of coffee pulp/animal/day replacing 1 kg of balanced feed). Weekly records were kept on milk production and quality, somatic cell count (SCC), milk ureic nitrogen (MUN), as well as body condition score of the animals. Information on the costs of the evaluated diets was also collected. Repeated measures were analyzed over time using a mixed linear model with the statistical software R, with a Tukey test to determine the significance (p < 0.05) between treatments. No significant differences (p ˃ 0.05) were found for any of the variables of production, milk quality, and body condition score for the evaluated treatments. However, a 3.4% reduction in the cost of the diet was achieved with the inclusion of 2 kg of dehydrated coffee pulp (Treatment 2), maintaining the same performance in milk production and quality. Under the conditions of this research, it is concluded that supplementation with dehydrated coffee pulp did not affect the productive performance of cows in milk production but reduced the cost of feeding the animals, which should be valued as an advantage in dairy cattle diets.